2017
DOI: 10.12681/bgsg.14299
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity of Western Anatolian Plutons, Turkey

Abstract: The natural radioactivity of the Western Anatolian plutonic bodies (Turkey), as well as the assessment of any potential health hazard due to their usage as decorative building materials is studied. Seventy samples from Western Anatolian plutonic bodies, including various rock-types from quartz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…During the Cenozoic Era, western Anatolia experienced intensive magmatic activity represented by volcanic and plutonic rocks (Figure 2). Several authors have reported the geology, geochemistry and tectonic configuration of these rocks (Şengör and Yılmaz, 1981;Yılmaz, 1989;Güleç, 1991;Harris et al, 1994;Altunkaynak and Yılmaz, 1998;Aldanmaz et al, 2000;Satır, 2000, 2006;Köprübaşı and Aldanmaz, 2004;Altunkaynak andDilek, 2006, 2013;Altunkaynak, 2007, 2010;Altunkaynak and Genç, 2008;Boztuğ et al, 2009;Ersoy et al, 2009;Erkül, 2010Erkül, , 2012Hasözbek et al, 2010;Altunkaynak et al, 2010Altunkaynak et al, , 2012aAltunkaynak et al, , 2012bErkül and Erkül, 2012;Erkül et al, 2013, Papadopoulos et al, 2016. The plutonic rocks are represented by I type granitoids and medium to high potassium calc alkaline rocks (Harris et al, 1994;Köprübaşı and Aldanmaz, 2004;Altunkaynak, 2007;Altunkaynak et al, 2012a).…”
Section: Geology Of Western Anatoliamentioning
confidence: 99%
“…During the Cenozoic Era, western Anatolia experienced intensive magmatic activity represented by volcanic and plutonic rocks (Figure 2). Several authors have reported the geology, geochemistry and tectonic configuration of these rocks (Şengör and Yılmaz, 1981;Yılmaz, 1989;Güleç, 1991;Harris et al, 1994;Altunkaynak and Yılmaz, 1998;Aldanmaz et al, 2000;Satır, 2000, 2006;Köprübaşı and Aldanmaz, 2004;Altunkaynak andDilek, 2006, 2013;Altunkaynak, 2007, 2010;Altunkaynak and Genç, 2008;Boztuğ et al, 2009;Ersoy et al, 2009;Erkül, 2010Erkül, , 2012Hasözbek et al, 2010;Altunkaynak et al, 2010Altunkaynak et al, , 2012aAltunkaynak et al, , 2012bErkül and Erkül, 2012;Erkül et al, 2013, Papadopoulos et al, 2016. The plutonic rocks are represented by I type granitoids and medium to high potassium calc alkaline rocks (Harris et al, 1994;Köprübaşı and Aldanmaz, 2004;Altunkaynak, 2007;Altunkaynak et al, 2012a).…”
Section: Geology Of Western Anatoliamentioning
confidence: 99%